Easy Cane / Siti Aisyah Abdullah ... [et al.] - Abdullah, Siti Aisyah; Mohammad Nizam, Puteri Nur Najihah; Mustaza, Nur Fatihah Nabilah; Zulfika, Zulaikha Nuryn; Azman, Siti Aisyah; Hairulanuar, Nurulhusna Najihah; Mohd Nazley, Muhammad Syafiq (2022)
Easy Cane is designed after thorough research and discussions has been taken into consideration. From the outcome of our research, the standard canes lack important features that can be fully utilized by the visually impaired or blind person. The design of Easy Cane takes into consideration the cost, performance, reliability, safety, material, and durability. The technology used in the Easy Cane was rather affordable in accordance with the other existing smart cane that is available in the market. For instance, Easy Cane helps visually impaired, or blind person to know whenever there are any obstacles around them such as cracks and holes. To ensure our place in this market, thorough research and market surveys have also been conducted. Our product which is Easy Cane's target market is aim for the blind and visually impaired people to allow them easily in navigating outdoor environments. As there are many smart canes in the market, we manage to make our product Easy Cane different with additional of other unique features with affordable price as compared to the other canes available in the market. Easy Cane has special features as it has been given a unique touch to the product as well as suits the user’s preference. Easy Cane uses several approaches to sell the product, which are through e-Commerce platforms such as Shopee and Astro GO Shop. We also sell our product at pharmacies and some selected stores in Malaysia. The company target for the production after the first year will increase to 3 percent for the first year.